Strengthening Family Roles Through Islamic Educational Strategies to Promote Halal Lifestyle Among Muslim Minority Youth in Vietnam - Warsiyah; Agus Irfan; Agung Nugroho; Safa'ah Nur Fa'izin; Thi Safinah (Dimas: Jurnal Pemikiran Agama untuk Pemberdayaan, 2025)
Muslim minority families in Vietnam face limited access to structured Islamic education and halal literacy resources, leading to challenges in strengthening halal lifestyle awareness among adolescents. Responding to this issue, this community engagement program was conducted in August 2025 at Thánh đường Hồi Giáo Dầu Tiếng, Ho Chi Minh City, involving 10 Muslim families. The program employed a participatory family empowerment model, utilizing a combination of online assessments, offline workshops, and hybrid mentoring and evaluation. Vietnamese students from Universitas Wahid Hasyim supported the on-site implementation, while practitioners from Indonesia provided guidance online. Over one month of staggered activities, families participated in halal literacy education, Prophetic parenting training, and the development of a Halal Lifestyle Family Plan (HLFP). The results show increased parental awareness of halal values, improved family communication, and observable behavioral changes among adolescents in consumption habits, digital media use, and Islamic identity confidence. This program demonstrates that a culturally responsive, hybrid, and family-centered Islamic educational strategy can effectively strengthen halal lifestyle practices within Muslim minority contexts.